ANTIMICROBIAL ACTIVITY, ALONE AND IN CONJUNCTION WITH CEFUROXIME - amna naz; Sadia Haider; Syed Muhammad Ali (International Journal of Pharmacy & Integrated Health Sciences)
Introduction: Occurrence of multidrug resistant microorganism is the result of irrational use of antibiotics. Recently essential oil, an important constituent of therapeutic and scented plant has been explored for their antimicrobial activity. Objectives: In this study, antibacterial activities of rosemary essential oil (REO) alone and also in conjunction with beta lactam antibiotic cefuroxime (CXM) were assessed. The purity of REO was checked by gas chromatography / mass spectrophotometry method (GC-MS). Methodology: By agar well diffusion method for REO and its diluents with dimethyl sulfoxide (DMSO) and tween 80, the zone of inhibition (ZOI) against four Gram positive bacterial strains of Bacillus subtilis, Bacillus cereus, Staphylococcus aureus, and Staphylococcus epidermidis and three Gram negative bacterial strains of Pseudomonas aeruginosa (1:2,1:10, 1:20, 1:40 and 1:50). E. coli as bacterial and DMSO as solvent were used as a control. Results: Antimicrobial activity was found to be highest against Staphylococcus aureus with ZOI 17.56mm and the lowest against Pseudomonas aeruginosa with ZOI 5.53 mm. The combination of REO and CXM indicated synergistic effects against E. coli, Staphylococcus aureus, Klebsiella pneumonia and Proteus mirabilis and antagonistic effect against Pseudomonas aeruginosa and indifferent effects against Bacillus subtilis and bacillus epidermidis based on fractional inhibitory concentration (FIC) values. The t test was applied to FIC values that showed significant p value (< 0.5). Conclusion:  In conclusion, the antibacterial activity of the REO and CXM was enhanced when administered in combination, with the exception of Pseudomonas aeruginosa. In future this study may lead the way to the development of new drug combinations and dosage forms for increased antimicrobial and a reduced resistance against common pathogens.